Manajemen Kolaboratif Sebagai Pendekatan Efektif Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) di Sekolah Dasar - Hamidaturrohmah, Hamidaturrohmah; Rohman, Nur; Munir, Muhammad Misbahul (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Pancasila as the basis of the Indonesian state has an important role in shaping the character and identity of the nation. Effective implementation P5 requires collaborative management involving various parties, such as school principals, teachers, education staff, parents and the community. This research aims to describe the urgency of collaborative management as an effective approach in implementing P5 in elementary schools. Research method used in this research is a qualitative method with a type of literature study. The literature study was carried out by developing theoretical and practical aspects obtained from collecting data from national and international journals that are still relevant. So the results of the study support the ideas and concepts of this research. Based on literature analysis, it shows that collaborative management is used as an effective approach in implementing P5 in elementary schools, including the steps summarized in 4M, building open and effective communication with parents and communities involved in implementing P5, second, providing a clear division of roles for students. and the stakeholders involved, third, encourage active involvement of all parties from planning, implementation to evaluation. fourth, increasing collaboration in sharing insights activities between teachers and school principals so that P5 can be understood together